Soils of the Chaco Region - Moretti, Lucas Martin; Morras, Hector; Pereyra, Fernando X.; Schulz, Guillermo (Springer, 2024)
The Argentinian Chaco region belongs to an extensive ecoregion called “Great Chaco”, characterized by ample plains of fluvial aggradation and linked to the formation of large alluvial fans. The climate is semi-arid to humid, with marked dry season and important seasonal water deficit. The vegetation includes deciduous dry forests, shrubs and grassland steppes, palm groves, woodlands and savannas. The soil parent materials are fluvial, lacustrine and eolian (e.g. primary and reworked loess) sediments. The distribution of soils has three clearly defined areas: a semi-arid central-Western sector, enclosed by a humid narrow strip to the West, and a more extended humid area to the East, close to Paraná–Paraguay rivers. According to the available cartography, the dominant soils are Mollisols and Alfisols, followed by Entisols, Inceptisols and Aridisols. Vertisols were also identified in the West and in the south-eastern border of the region. The main pedogenetic processes are basically melanisation and argilluviation in the wettest areas and melanisation, calcification, alkalinization and salinization in the driest areas. On the other hand, hydromorphic and vertisolization processes occur in closed depressions. The soils of the Chaco region are ver y susceptible to wind and water erosion, especially during the dry season and in bare soils. In general, the soils are devoted to the production of cotton, sugar cane and to the livestock industry. In the southern part of the region, agriculture of cereal and oilseed grains becomes dominant.